Visceral Adiposity Index was a useful Predictor of Prediabetes - Gu, Dongfeng; Ding, Yanan; Zhao, Yunfeng; Qu, Qingshan (Experimental and Clinical Endocrinology & Diabetes, 2018)
Aim To study the relationship of visceral adiposity index (VAI) and prediabetes and the power of which in predicting of prediabetes.Methods A cross-sectional epidemiological survey was conducted. All participants were divided into four groups: VAI and WC (both are normal), VAI↑ and WC (postcritical VAI and normal WC), VAI and WC↑ (Normal VAI and postcritical WC), and VAI↑ and WC↑ (postcritical VAI and postcritical WC). A multivariate logistic analysis was used to analyze the relationship between the four groups and prediabetes, and diabetes. A receiver operating characteristic (ROC) curve analysis was used to evaluate the accuracy of predictions for prediabetes and diabetes.Results Both VAI and WC were independent risk factors of Prediabetes. The ORs for Prediabetes in the VAI↑&WC group were 1.641 (95%CI 1.146–2.349), P=0.007, in males, in Model 2. The ORs for Prediabetes in the VAI&WC↑ group were 1.454 (95%CI 1.055–2.005), P=0.022, in males, in Model 2. The ORs for Prediabetes in the VAI↑&WC group were 2.305 (95%CI 1.623–3.273), P=0.000, in females, in Model 2. The ORs for Prediabetes in the VAI&WC↑ group were 1.997 (95%CI 1.529–2.608), P=0.000, in females, in Model 2. The AUC value of VAI were 0.601 (95%CI 0.568–0.634), P=0.000, in prediabetes of men; which were 0.645 (95%CI 0.618–0.672), P=0.000, in prediabetes women. WC had the highest AUC value of 0.605 (95%CI 0.571–0.638), P=0.000, in prediabetes of men, also had the highest of AUC value of 0.673 (95%CI 0.648–0.697), P=0.000, in prediabetes of women.Conclusion VAI was positively associated with prediabetes, and also a usefulindicator of prediabetes.
Keywords: visceral adiposity index; waist circumference; prediabetes; diabetes